School Or Madrasah-Based Quality Improvement Management In Integrated Quality Management Of Education From An Islamic Perspective - Nurul Hidayati; Maemunah Sa’diyah; Ahmad Sastra (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
School or madrasa-based quality improvement management is an essential effort to enhance the quality of education, especially from an Islamic perspective. In Islam, education is not only seen as an intellectual process but also as a means to enhance faith and morals. Therefore, the management of education must pay attention to Islamic values, which include tawhid, akhlakul karimah, ihsan, and justice. Additionally, quality education is influenced by the development of teacher competencies, the use of technology in learning, and the development of curricula that are relevant to the needs of the times. Education in Islam emphasizes the importance of knowledge, as reflected in various verses of the Qur'an that honor knowledge. As an implementation of this principle, education must integrate academic knowledge with moral and spiritual values. To achieve high-quality education, educational management must apply effective managerial principles, including planning, organizing, implementing, and evaluating based on quality standards. From the perspective of Islamic educational management, integrated quality development is carried out by incorporating Islamic values into the education system, improving teacher quality through continuous training, and utilizing technology to enhance learning quality. Good management can strengthen the role of schools/madrassas in creating a safe, comfortable, and productive educational environment, as well as preparing students to become individuals who are faithful, virtuous, and competent in their fields.